(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The experiment was conducted with the objective to study the variability and the character association for reproductive traits in exotic and local onion genotypes. Ten genotypes of onion (Allium cepa L) collected from different sources, namely; Indian medium (G1), Indian medium (G2), Indian small (G3), Taherpuri (G4), Patnai pink (G5), Patnai small (G6), Big single bulb (G7), Big double bulb (G8), Small single bulb (G9), Small double bulb (G10) were included in the study. Significant variations were observed among the genotypes for all the characters at 1% level except umbel diameter. This indicates that there is a wide genotypic variation among the genotypes for all the characters studied except umbel diameter. Considering genetic parameters, high GCV values were observed for days to 100% sprouting, number of unfilled seeds per umbel, number of filled seeds per umbel, number of flowers per umbel, number of seeds per umbel, number of seeds per plant and seed yield per umbel (gm). High heritability values with high genetic advances in percent of mean were obtained for days to 100% sprouting, days to 50% bolting, number of unfilled seeds per umbel and seed yield per umbel (gm). Correlation analysis indicated significant positive genotypic and phenotypic correlation coefficient of number of seeds per plant, 100 seed weight (gm), number of seeds per umbel and number of unfilled seeds per umbel with seed yield per umbel (gm). Number of flowers per umbel and number of filled seeds per umbel had the highest positive direct effect on seed yield (gm). Days to 100% sprouting, umbel diameter and number of seeds per plant had direct negative effect on seed yield. Path analysis exhibited that highly significant positive correlation with positive direct effect showed for number of filled seeds per umbel (1.87), number of flowers per umbel (1.52) and 100seed weight (0.74g). Days to 50% bolting, number of seeds per plant, number of flowers per umbel, number of filled seeds per umbel, number of unfilled seeds per umbel and seed yield per umbel could be selected as yield contributing characters in onion.